4D Marketing Mix Terhadap Keputusan Pembelian pada Shopee di Kota Surakarta - Dewi Aprilia Nugraheni; Esti Dwi Rahmawati; Agus Suyatno (Master Manajemen, 2024)
This research aims to analyze the influence of disruption, diffusion, digitalization, and de-siloage on purchasing decisions. This research uses a primary data collection method, namely by distributing questionnaires where the population in this research is Shopee users in Surakarta City. Sampling in this study used a non-probability sampling technique using purposive sampling. With a sample size of 100 respondents. The analysis method is multiple linear regression analysis using SPSS 25 software. The results of this research show that disruption has a positive and significant effect on purchasing decisions, diffusion has a positive and significant effect on purchasing decisions, digitalization has a positive and significant effect on purchasing decisions, and de-siloage has a positive effect and significant to purchasing decisions.